ANALISIS PENGARUH FILM CRAYON SINCHAN TERHADAP KARAKTER SISWA - Halimatus Sakdiah, Imah; Safarani Jannah, Vidyah; Salsabila, Zakia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of the Crayon Shinchan film on the character development of elementary school students. The background of the research arises from the phenomenon that entertainment media, particularly animated films, have a strong appeal to children and the potential to shape both positive and negative behaviors. The method used is content analysis by observing the episode Pantsu O Kai Ni Iku Zo through thematic coding of verbal behavior, physical gestures, social interactions, and implicit messages displayed. The results of the study show a dominance of negative behaviors such as vulgar humor, teasing, and lack of self-control exhibited by both the main and supporting characters. These findings align with Bandura’s Observational Learning theory, which states that children tend to imitate behaviors they observe in media. The messages contained in the show are ambiguous, explicitly emphasizing entertainment but implicitly normalizing impolite behavior. This contrasts with educational shows such as Upin & Ipin, which emphasize values of social care and friendship. The study highlights the importance of parental and teacher guidance in directing children to choose shows that align with character education values, as well as the need for regulation of children’s programming in Indonesia.